NEDD4L downregulates autophagy and cell growth by modulating ULK1 and a glutamine transporter - Lee, Dong-Eun (Cell Death Dis, 2020)
In mammals, autophagosome formation is initiated by ULK1 via the posttranslational modification of this protein. However, the precise role of ULK1 ubiquitination in modulating autophagy is unknown. Here, we show that NEDD4L, an E3 ubiquitin ligase, binds ULK1 in pancreatic cancer cells. ULK1 expression was stabilized in NEDD4L knockdown cells compared to that in control cells, suggesting that NEDD4L is involved in ULK1 ubiquitination and its subsequent degradation. Autophagy activity was enhanced in NEDD4L knockdown cells compared to control cells. NEDD4L-depleted cells exhibited an increase in the cellular oxygen consumption rate (OCR) and mitochondrial membrane potential, and maintained mitochondrial fusion status in response to metabolic stress. Enhanced OCR and mitochondrial fusion morphology in NEDD4L knockdown cells were repressed by siRNA targeting ULK1. In addition to ULK1, ASCT2, a glutamine transporter, was accumulated in NEDD4L-depleted cells; this is important for maintaining autophagy activation and mitochondrial metabolic function. Finally, the cellular growth and survival rate increased in NEDD4L knockdown cells compared to control cells. However, the genetic or pharmacological blockade of either ULK1 or ASCT2 in NEDD4L-depleted cells sensitized pancreatic cancer cells, particularly in response to nutrient deprivation. In a mouse xenograft model of pancreatic cancer, the use of autophagy inhibitors suppressed tumor growth more in NEDD4L-depleted cells than in tumors from control cells. NEDD4L and ULK1 levels were inversely correlated in two different pancreatic cancer mouse models-xenograft mouse and KPC mouse models. These results suggest that NEDD4L suppressed autophagy and mitochondrial metabolism by reducing cellular ULK1 or ASCT2 levels, and thus could repress the growth and survival of pancreatic cancer cells. Therefore, ubiquitin ligase-mediated autophagy plays a critical role in regulating mitochondrial metabolism, thereby contributing to the growth and survival of certain cancers with low NEDD4L levels.